2018
DOI: 10.1016/j.abrep.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Excluded, then inebriated: A preliminary investigation into the role of ostracism on alcohol consumption

Abstract: IntroductionOstracism has only recently been investigated as a relevant social stressor that might precede college student alcohol use. The present study continues initial efforts to examine the effects of ostracism on subsequent alcohol consumption in the laboratory. A 2 (sex: male, female) × 2 (condition: ostracism, control) between-subjects experimental design was conducted to examine the effects of these variables on alcohol consumption in the laboratory.MethodsSocial drinking college students (N = 40; 43%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Previous studies have confirmed that social exclusion is one antecedent of Facebook addiction as well as internet addiction ( Poon, 2018 ; Lim, 2019 ; Arslan and Coşkun, 2021 ). Some scholars have also found that social exclusion can positively and significantly predict substance use disorder and other addictive behaviors ( Rabinovitz, 2014 ; Bacon and Engerman, 2018 ; Wesselmann and Parris, 2021 ). Likewise, consistent with H1, the results of the present study also demonstrated that social exclusion is a significant and positive predictor of smartphone addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that social exclusion is one antecedent of Facebook addiction as well as internet addiction ( Poon, 2018 ; Lim, 2019 ; Arslan and Coşkun, 2021 ). Some scholars have also found that social exclusion can positively and significantly predict substance use disorder and other addictive behaviors ( Rabinovitz, 2014 ; Bacon and Engerman, 2018 ; Wesselmann and Parris, 2021 ). Likewise, consistent with H1, the results of the present study also demonstrated that social exclusion is a significant and positive predictor of smartphone addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing such links causally is difficult, if not impossible, given the ethical and practical issues with studying misuse behaviorally. To our knowledge, there is only one experiment that directly examines substance use as a dependent outcome after experiencing social exclusion (Bacon and Engerman, 2018). This study found a marginally significant increase in the amount of alcohol consumed by excluded (vs. included) participants in an online interaction.…”
Section: Social Exclusion Trauma and Substance (Mis)usementioning
confidence: 69%
“…Although inconsistent with hypotheses, other laboratory studies also have failed to find the effects of SA on alcohol outcomes. Emerging adults may be warier about consuming alcohol offered by strangers, particularly in a sample with a majority of women in a novel or potentially unsafe context (Bacon & Engerman, 2018; Bacon et al, 2015). As both substances were offered in random order, participants may have considered using cannabis to be a safer way of engaging with the social context.…”
Section: Discussionmentioning
confidence: 99%